Tall cell carcinoma with reversed polarity: A case report of a very rare breast tumor entity and mini‐review. Issue 4 (2nd February 2021) - Trihia, Helen J.; Lampropoulos, Pavlos; Karelis, Loukas; Souka, Efthymia; Galanopoulos, Georgios; Provatas, Ioannis
Abstract: Tall cell carcinoma with reversed polarity (TCCRP) is a very rare variant of carcinoma of the breast, resembling the tall cell variant of papillary thyroid carcinoma, first described in 2003, recently recognized as a separate entity in the 5th edition of the WHO (World Health Organization) Blue Book Classification of breast tumors with alternative terminology of tall cell variant of papillary breast carcinoma and solid papillary carcinoma with reversed polarity. Here, we report an additional case of this rare tumor in a 71‐year‐old woman, and the problems correlating with its diagnosis.